Preparation method and application of silicon-carbon negative electrode material
By using porous carbon and a deposition agent to perform silicon deposition in the preparation of silicon carbon negative electrode materials, and using segmented carbon coating and composite carbon source gas methods, the problems of safety risks and low production efficiency in the prior art are solved, and the problem of low production efficiency is achieved. It provides efficient and safe production of silicon carbon anode material and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411585509.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
The existing silicon-carbon anode material preparation methods have problems such as safety risks, high temperature demand and low production efficiency, which affect product quality and feasibility of large-scale production.
Porous carbon is used as the matrix and silicon deposition is deposited in combination with a deposition agent. The reaction temperature and coating time are reduced by the method of segmented carbon coating and composite carbon source gas, and the production safety and product quality are improved.
It realizes efficient and safe production of silicon carbon anode materials, improves the silicon load and electrochemical performance of the product, and reduces the generation and resistivity of invalid silicon.
Smart Images

Figure CN119447274A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion batteries, and in particular relates to a preparation method of a silicon-carbon negative electrode material and an application thereof. Background Art
[0002] With the development of battery technology and applications, the energy density of lithium batteries is increasingly required. For negative electrode materials, traditional graphite negative electrodes are close to the theoretical specific capacity, while materials such as silicon dioxide will produce large volume changes during the charging and discharging process, which has defects. Silicon-carbon negative electrode materials that combine nano-silicon with porous carbon can effectively solve the above problems, but the preparation method of such silicon-carbon negative electrode materials still needs to be improved.
[0003] Patent CN115172691A describes a method of preparing silicon-carbon negative electrode by chemical vapor deposition using graphite carbon rope and silane as raw materials. This method has high requirements for raw materials. At the same time, the product obtained will expand during use due to the lack of support from porous carbon pore structure. Patent CN117352703A describes a method for preparing multi-level silicon-carbon negative electrode materials, in which the silicon deposition temperature reaches 700°C and the carbon coating temperature is as high as 900°C. Excessive temperature will bring greater safety risks. Patent CN117163945A uses liquid silane and carbon in a tubular furnace to react to prepare silicon-carbon negative electrode materials. This method has poor mass transfer and heat transfer during the reaction process, and its reaction temperature is as high as 1500°C. Product performance and production safety will greatly restrict actual production.
[0004] Therefore, there is still a need to develop a safe and efficient method for preparing silicon-carbon negative electrode materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a silicon-carbon negative electrode material, which can be more efficient and safe and has better product quality.
[0006] Another object of the present invention is to provide an application of the silicon-carbon negative electrode material.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0008] A method for preparing a silicon-carbon negative electrode material, characterized in that it comprises the following steps:
[0009] 1) Drying the porous carbon as a substrate;
[0010] 2) mixing the porous carbon substrate obtained in step 1) with a deposition aid and placing it in a reactor, introducing a protective gas, heating to a deposition temperature, introducing a mixture of a silicon source gas and a protective gas, and depositing silicon into the porous carbon;
[0011] 3) adjusting to a first coating temperature, introducing a mixture of carbon source gas 1 and protective gas to perform preliminary carbon coating on the porous carbon; then adjusting to a second coating temperature, introducing a mixture of carbon source gas 1, carbon source gas 2 and protective gas to perform complete carbon coating on the surface of the porous carbon;
[0012] 4) Cooling the reaction product, separating the deposition aid, and obtaining the silicon-carbon negative electrode material.
[0013] In some specific embodiments, the BET specific surface area of the porous carbon in step 1) is greater than 1500 m 2 / g, particle size less than 20 microns;
[0014] Preferably, the water content of the porous carbon substrate after drying is less than 2 wt %.
[0015] In some specific embodiments, the deposition aid in step 2) is at least one of ceramic balls, stainless steel balls, zirconium oxide balls, and silicon dioxide balls;
[0016] Preferably, the particle size of the deposition aid is 0.5-5 mm and the bulk density is greater than 1.5 g / cm 3 ;
[0017] More preferably, the mixing mass ratio of the porous carbon matrix to the deposition aid is 10:1 to 10:5.
[0018] In some specific embodiments, the protective gas is one or more of hydrogen, nitrogen or helium, and the protective gas flow rate is preferably 0.2-5m 3 / h;
[0019] Preferably, the deposition temperature is 400-560°C.
[0020] In some specific embodiments, the silicon source gas is one or more of monosilane, disilane, and chlorosilane;
[0021] Preferably, the mixing volume ratio of the silicon source gas and the protective gas is 1:10 to 6:10;
[0022] More preferably, the silicon source gas is introduced for 8-16 hours.
[0023] In some specific embodiments, the carbon source gas 1 in step 3) is one or more of methane, ethylene, and acetylene; the carbon source gas 2 is one or more of benzene, toluene, and naphthalene;
[0024] Preferably, the mixing volume ratio of the carbon source gas 1 to the protective gas is 1:10 to 4:10; the mixing volume ratio of the carbon source gas 2 to the protective gas is 1:3 to 3:1;
[0025] More preferably, the carbon source gas 1 is introduced for 1-4 hours, and the carbon source gas 1 and the carbon source gas 2 are mixed and introduced for 1-3 hours.
[0026] In some specific embodiments, the first coating temperature is 500-600°C, and the second coating temperature is 480-600°C.
[0027] In some specific embodiments, the reactor is a rotary kiln reactor.
[0028] In some specific embodiments, the separation method of the deposition aid is screening or air flow classification.
[0029] Another aspect of the present invention is the use of the silicon-carbon negative electrode material prepared by the above-mentioned preparation method in lithium-ion batteries.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention discloses a method for preparing a silicon-carbon negative electrode, which improves the deposition effect by adding a deposition aid, improves the silicon deposition efficiency, reduces the generation of invalid silicon, adopts segmented carbon coating and composite carbon source gas, reduces the reaction temperature and coating time, improves production safety, improves product quality, and can realize large-scale safe and efficient production of silicon-carbon negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic flow chart of the method for preparing the silicon-carbon negative electrode material of the present invention. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with embodiments, but the present invention is not limited to the listed embodiments, and should also include equivalent improvements and modifications of the technical solutions defined in the claims attached to the present application.
[0034] like Figure 1 As shown, the preparation method of the silicon-carbon negative electrode material of the present invention includes several steps of drying, mixing, deposition reaction, primary coating, secondary coating, and separation. Specifically, it includes the following steps:
[0035] 1) Drying the porous carbon as a substrate;
[0036] 2) mixing the porous carbon substrate obtained in step 1) with a deposition aid, placing them together in a reactor, introducing a protective gas, heating to a deposition temperature, introducing a mixture of a silicon source gas and a protective gas to carry out a deposition reaction, and depositing silicon into the porous carbon;
[0037] 3) adjusting the reactor to a first coating temperature, introducing a mixture of carbon source gas 1 and protective gas, and performing a primary carbon coating on the porous carbon; then adjusting the reactor to a second coating temperature, introducing a mixture of carbon source gas 1, carbon source gas 2 and protective gas for secondary coating, and completing complete carbon coating on the surface of the porous carbon;
[0038] 4) Cooling the reaction product, separating the deposition aid, and obtaining the silicon-carbon negative electrode material.
[0039] In step 1) of the present invention, the BET surface area of the raw porous carbon is greater than 1500 m 2 / g, for example 1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g, etc., with a particle size of less than 20 microns, such as 19 microns, 18 microns, 17 microns, 15 microns, 13 microns, 10 microns, etc.;
[0040] In step 1) of the present invention, heating drying is adopted, and there is no particular restriction on the heating method. The drying temperature is greater than 120°C, for example, 150°C, 160°C, 170°C, etc., and the water content of the matrix after drying is less than 2wt%, for example, 1.9wt%, 1.8wt%, 1.7wt%, 1.6wt%, 1.5wt%, 1.3wt%, 1.0wt%, etc.
[0041] In step 2) of the present invention, a deposition aid is used to improve the deposition effect. The mass ratio of the porous carbon matrix to the deposition aid is 10:1 to 10:5, such as 10:1, 10:2, 10:3, 10:4, 10:5, etc.; the deposition aid is any one of ceramic balls, stainless steel balls, zirconia balls, and silica balls, and the particle size of the deposition aid is 0.5-5mm, such as 1mm, 2mm, 3mm, 4mm, 5mm, etc., and the bulk density is greater than 1.5g / cm 3 , for example 1.6 g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3Etc. On the one hand, the deposition aid can enhance solid heat transfer, solve the problem of solid heating difficulties in rotary kiln equipment, reduce the temperature difference between the heating wall and the material, and improve safety; at the same time, it can enhance the mass transfer between solid (porous carbon) and gas (silicon source gas, carbon source gas), which can greatly improve the efficiency of chemical vapor deposition; on the other hand, silicon deposition of silicon source gas will occur simultaneously inside and outside the porous carbon pores. Silicon deposition outside the porous carbon will cause the resistivity of silicon-carbon negative electrode materials to increase, and even powdered products to agglomerate, and product quality will decrease. The presence of the deposition aid can greatly reduce silicon deposition outside the porous carbon, reduce the generation of invalid silicon, and improve product quality.
[0042] In the present invention, the protective gas used is one or more of hydrogen, nitrogen or helium, and the protective gas flow rate is 0.2-5m 3 / h, for example 3m 3 / h、3.5m 3 / h、4m 3 / h、4.5m 3 / h, etc.; due to the presence of the deposition aid, the deposition temperature can be reduced to 400-560°C, which improves the safety of the reaction. At the same time, the temperature reduction also reduces the generation of elemental silicon from the silicon source gas in the gas phase to a certain extent, thereby improving the selectivity and effective conversion of the reaction; the mixed volume ratio of the silicon source gas and the protective gas is 1:10 to 6:10, for example, 2:10, 3:10, 4:10, 5:10, etc.; the silicon source gas introduction time is 8-16h, for example, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc.
[0043] In step 3) of the present invention, the segmented carbon coating method is adopted to effectively improve the coating effect, and the coating method of the composite carbon source gas can reduce the coating temperature and improve the production safety. Among them, the carbon source gas 1 is one or more of methane, ethylene, and acetylene; the carbon source gas 2 is one or more of benzene, toluene, and naphthalene; the decomposition mechanisms of the carbon source gas 1 and the carbon source gas 2 at high temperature are different, the molecular size of the carbon source gas 1 is small, and the diffusion speed is fast, which is conducive to entering the porous carbon channel for preliminary coating; the carbon source gas 2 decomposes at high temperature to produce free radicals, and then reacts with the carbon source 1, reducing the reaction activation energy, reducing the reaction temperature, and greatly improving the safety of large-scale production; at the same time, the carbon source gas 2 molecule has a high carbon content, which improves the carbon coating efficiency, shortens the coating time, reduces the residence time of the nano-silicon generated in step 2 at high temperature, reduces the transformation of effective nano-silicon to invalid silicon, and improves product quality.
[0044] In step 3) of the present invention, the volume ratio of the carbon source gas 1 and the protective gas is 1:10 to 4:10, for example, 2:10, 3:10, etc.; the volume ratio of the carbon source gas 2 and the protective gas is 1:3 to 3:1, for example, 2:1, etc.; the introduction time of the carbon source gas 1 is 1-4h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc., and the introduction time of the carbon source gas 1 and the carbon source gas 2 is 1-3h, for example, 2h, 3h, etc.
[0045] In the present invention, the protective gas is continuously introduced, and the reaction time is controlled by controlling the introduction time of the silicon source gas and the carbon source gas.
[0046] The present invention adopts a method of segmented carbon coating and composite carbon source gas. Compared with a simple carbon coating process, the coating temperature can be as low as 500-600°C, and the secondary coating temperature can be as low as 480-600°C, thereby improving production safety and product quality.
[0047] The silicon source gas used in the present invention is one or more of monosilane, disilane and chlorosilane.
[0048] The reactor used in the present invention is a rotary kiln reactor, and the rotation speed of the rotary kiln is not particularly limited, for example, it is 0.5-5 rpm, such as 1 rpm, 2 rpm, 3 rpm, 4 rpm, etc., and the filling rate of the rotary kiln is 5-20%, such as 10%, 12%, 15%, 18%, etc.
[0049] The deposition aid separation method used in the present invention is screening or airflow classification, for example, a vibrating screen is used to separate the deposition aid. The specific separation process can be achieved by conventional technical means in the art.
[0050] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0051] The main raw material specifications used in the embodiment are as follows:
[0052] Porous carbon: particle size 1-10 μm, specific surface area 1750 m 2 / g;
[0053] Deposition aid: zirconium oxide particles, particle size about 3mm, bulk density about 2.5g / cm 3 ;
[0054] Silicon source gas: pressure 80-120 bar, purity ≥99.999%;
[0055] Carbon source gas 1: pressure ≥ 0.3 barg, purity ≥ 95%;
[0056] Carbon source gas 2: liquid raw material with purity ≥98% is used for vaporization, with inlet temperature of 200-300℃ and pressure of 0.1-0.3barg
[0057] Example 1
[0058] 30 kg of porous carbon was added to a rotary dryer and dried at 300 °C for 4 h to obtain a porous carbon matrix with a water content of 0.3%. The matrix was mixed evenly with 10 kg of a deposition aid with a particle size of 1 mm and a bulk density of 3 g / cm 3 , added to a 1500L rotary kiln, at 5m 3 / h gas flow into the rotary kiln. Raise the temperature of the rotary kiln to 480℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of monosilane into the rotary kiln, and after 12h of ventilation, the monosilane intake is terminated. The temperature of the rotary kiln is raised to 540℃ at 10℃ / min and kept constant. 3 / h flow rate of acetylene into the rotary kiln for 1 hour. Keep the acetylene flowing, and at the same time, flow benzene vapor into the rotary kiln at a flow rate of 3kg / h. After the flow time of 3 hours, stop the flow of acetylene and benzene. Lower the temperature of the rotary kiln to below 60°C, and use a 300-mesh vibrating screen to screen the material to obtain a silicon-carbon negative electrode material.
[0059] Example 2
[0060] 30 kg of porous carbon was added to a rotary dryer and dried at 300 °C for 4 h to obtain a porous carbon matrix with a water content of 0.5%. The matrix was mixed evenly with 10 kg of a deposition aid with a particle size of 1 mm and a bulk density of 3 g / cm 3 , added to a 1500L rotary kiln, at 5m 3 / h gas flow into the rotary kiln. Raise the temperature of the rotary kiln to 480℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of monosilane into the rotary kiln, and after 12h of ventilation, the monosilane intake is stopped. The temperature of the rotary kiln is raised to 580℃ at 10℃ / min and kept constant. 3 / h flow rate of acetylene into the rotary kiln for 1 hour. Keep the acetylene flowing, and at the same time, flow benzene vapor into the rotary kiln at a flow rate of 5kg / h. After the flow time is 1.8 hours, stop the flow of acetylene and benzene. Lower the temperature of the rotary kiln to below 60°C, and use a 300-mesh vibrating screen to screen the material to obtain a silicon-carbon negative electrode material.
[0061] Example 3
[0062] 30 kg of porous carbon was added to a rotary dryer and dried at 300 °C for 4 h to obtain a porous carbon matrix with a water content of 0.4%. The matrix was mixed evenly with 10 kg of a deposition aid with a particle size of 1 mm and a bulk density of 3 g / cm 3 , added to a 1500L rotary kiln, at 5m3 / h gas flow into the rotary kiln continuously. Raise the temperature of the rotary kiln to 540℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of monosilane into the rotary kiln, after ventilation time of 8h, stop the monosilane intake. Raise the temperature of the rotary kiln to 540℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of acetylene into the rotary kiln for 1 hour. Keep the acetylene flowing, and at the same time, flow benzene vapor into the rotary kiln at a flow rate of 3kg / h. After the flow time of 3 hours, stop the flow of acetylene and benzene. Lower the temperature of the rotary kiln to below 60°C, and use a 300-mesh vibrating screen to screen the material to obtain a silicon-carbon negative electrode material.
[0063] Example 4
[0064] 30 kg of porous carbon was added to a rotary dryer and dried at 300 °C for 4 h to obtain a porous carbon matrix with a water content of 0.4%. The matrix was mixed evenly with 50 kg of a deposition aid with a particle size of 3 mm and a bulk density of 3 g / cm 3 , added to a 1500L rotary kiln, at 5m 3 / h gas flow into the rotary kiln. Raise the temperature of the rotary kiln to 420℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of monosilane into the rotary kiln, after ventilation time of 16h, the monosilane gas feeding is stopped. The temperature of the rotary kiln is raised to 510℃ at 10℃ / min and the temperature is kept constant. 3 / h flow rate of acetylene into the rotary kiln for 0.2h. Keep the acetylene flowing, and at the same time, flow benzene vapor into the rotary kiln at a flow rate of 10kg / h. After the flow time of 1h, stop the flow of acetylene and benzene. Lower the temperature of the rotary kiln to below 60℃, and use a 300-mesh vibrating screen to screen the material to obtain silicon-carbon negative electrode material.
[0065] Example 5
[0066] 30 kg of porous carbon was added to a rotary dryer and dried at 300 °C for 4 h to obtain a porous carbon matrix with a water content of 0.4%. The matrix was mixed evenly with 10 kg of a deposition aid with a particle size of 3 mm and a bulk density of 3 g / cm 3 , added to a 1500L rotary kiln, at 5m 3 / h gas flow into the rotary kiln. Raise the temperature of the rotary kiln to 410℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of disilane into the rotary kiln, after ventilation time of 12h, stop the introduction of monosilane. Raise the temperature of the rotary kiln to 580℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of ethylene into the rotary kiln for 2 hours. Keep ethylene flowing, raise the temperature of the rotary kiln to 600°C at 10°C / min and keep the temperature constant, then pass toluene vapor into the rotary kiln at a flow rate of 5kg / h. After the flow time of 2 hours, stop the flow of ethylene and toluene. Lower the temperature of the rotary kiln to below 60°C, and use a 300-mesh vibrating screen to screen the material to obtain a silicon-carbon negative electrode material.
[0067] Comparative Example 1
[0068] 30 kg of porous carbon was added to a rotary dryer and dried at 300 °C for 4 h to obtain a porous carbon matrix with a water content of 0.3%. The matrix was added to a 1500 L rotary furnace at 5 m 3 / h gas flow into the rotary kiln. Raise the temperature of the rotary kiln to 480℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of monosilane into the rotary kiln, and after 12h of ventilation, the monosilane intake is stopped. The temperature of the rotary kiln is raised to 580℃ at 10℃ / min and kept constant. 3 / h flow rate of acetylene into the rotary kiln, and after 8 hours of acetylene feeding, the acetylene feeding is stopped. The temperature of the rotary kiln is lowered to below 60°C to obtain a silicon-carbon negative electrode material.
[0069] Comparative Example 2
[0070] 30 kg of porous carbon was added to a rotary dryer and dried at 300 °C for 4 h to obtain a porous carbon matrix with a water content of 0.3%. The matrix was added to a 1500 L rotary furnace at 5 m 3 / h gas flow into the rotary kiln. Raise the temperature of the rotary kiln to 580℃ at 10℃ / min and keep the temperature constant. 3 / h flow rate of monosilane into the rotary kiln, and after the ventilation time is 12h, the monosilane intake is stopped. The temperature of the rotary kiln is raised to 700℃ at 10℃ / min and the temperature is kept constant. Acetylene is introduced into the rotary kiln at a flow rate of 5m3 / h, and after the ventilation time is 3h, the acetylene feeding is stopped. The temperature of the rotary kiln is reduced to below 60℃ to obtain a silicon-carbon negative electrode material.
[0071] The silicon-carbon negative electrode materials prepared in the examples and comparative examples were analyzed for silicon content using ICP emission spectroscopy.
[0072] The following method was used to make a battery to test the electrochemical performance: silicon-carbon negative electrode material was used as the negative electrode active material, and the negative electrode slurry was prepared by mixing the negative electrode active material, sodium carboxymethyl cellulose (CMC), conductive carbon black (SP), and styrene-butadiene rubber (SBR) in a mass ratio of 94.5:1.5:1.5:2.5. The slurry was coated on both sides of the copper foil current collector and vacuum dried to obtain the negative electrode plate. Ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate were mixed in a volume ratio of 1:1:1, and lithium hexafluorophosphate was added to obtain an electrolyte with a lithium salt concentration of 1 mol / L. The negative electrode plate and lithium sheet, electrolyte, and Celgard2400 separator were assembled, and the shell was assembled with a button battery using a conventional production process.
[0073] The button cell was charged and discharged at 0.1 times rate at 25°C, and the application performance test results are as follows.
[0074]
[0075] The results of the above embodiments and comparative examples show that the silicon-carbon negative electrode materials prepared in the embodiments have higher performance. The results of Example 1 and Comparative Example 1 show that under the same deposition conditions, the addition of a deposition aid can greatly increase the silicon loading of the product, and a product with higher capacity and performance can be obtained; the results of Example 1 and Comparative Example 2 show that in the absence of a deposition aid, the amount of silane required to achieve a similar deposition effect will increase significantly, and at the same time, the generation of invalid silicon on the surface of the product will increase, resulting in an increase in resistivity and serious material agglomeration. The results of Example 1, Example 2 and Comparative Example 2 show that the method of segmented carbon coating and composite carbon source gas can shorten the coating time at the same temperature, while improving the coating effect, and the product has a smaller specific surface area; the results of Example 1, Example 3 and Comparative Example 2 show that the method of segmented carbon coating and composite carbon source gas can reduce the coating temperature at the same time and with similar coating effects.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: 1) Drying the porous carbon as a substrate; 2) mixing the porous carbon substrate obtained in step 1) with a deposition aid and placing it in a reactor, introducing a protective gas, heating to a deposition temperature, introducing a mixture of a silicon source gas and a protective gas, and depositing silicon into the porous carbon; 3) adjusting to a first coating temperature, introducing a mixture of carbon source gas 1 and protective gas to perform preliminary carbon coating on the porous carbon; then adjusting to a second coating temperature, introducing a mixture of carbon source gas 1, carbon source gas 2 and protective gas to perform complete carbon coating on the surface of the porous carbon; 4) Cooling the reaction product, separating the deposition aid, and obtaining the silicon-carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The BET specific surface area of the porous carbon in step 1) is greater than 1500 m 2 / g, particle size less than 20 microns; Preferably, the water content of the porous carbon substrate after drying is less than 2 wt %.
3. The preparation method according to claim 1, characterized in that: The deposition aid in step 2) is at least one of ceramic balls, stainless steel balls, zirconium oxide balls, and silicon dioxide balls; Preferably, the particle size of the deposition aid is 0.5-5 mm and the bulk density is greater than 1.5 g / cm 3 ; More preferably, the mixing mass ratio of the porous carbon matrix to the deposition aid is 10:1 to 10:
5.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The protective gas is one or more of hydrogen, nitrogen or helium, and the protective gas flow rate is preferably 0.2-5m 3 / h; Preferably, the deposition temperature is 400-560°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The silicon source gas is one or more of monosilane, disilane and chlorosilane; Preferably, the mixing volume ratio of the silicon source gas and the protective gas is 1:10 to 6:10; More preferably, the silicon source gas is introduced for 8-16 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step 3), the carbon source gas 1 is one or more of methane, ethylene, and acetylene; the carbon source gas 2 is one or more of benzene, toluene, and naphthalene; Preferably, the mixing volume ratio of the carbon source gas 1 to the protective gas is 1:10 to 4:10; the mixing volume ratio of the carbon source gas 2 to the protective gas is 1:3 to 3:1; More preferably, the carbon source gas 1 is introduced for 1-4 hours, and the carbon source gas 1 and the carbon source gas 2 are mixed and introduced for 1-3 hours.
7. The preparation method according to claim 6, characterized in that: The first coating temperature is 500-600°C, and the second coating temperature is 480-600°C.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The reactor is a rotary kiln reactor.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The separation method of the deposition aid is screening or air flow classification.
10. Use of the silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 9 in lithium-ion batteries.
Citation Information
Patent Citations
High-density and high-purity silicon-carbon negative electrode material and preparation method thereof
CN115172691A
Homogeneous silicon-carbon negative electrode material and preparation method and application thereof
CN117163945A
Preparation method of multi-level silicon-carbon negative electrode material
CN117352703A
Cited By
Low-cost silicon-carbon negative electrode material and preparation method thereof
CN120998988A